Modern Clinical Guidelines for the Management of Patients with Gaucher Disease - Inga V. Anisimova; Galina V. Baydakova; Aleksander A. Baranov; Nato D. Vashakmadze; Elena A. Vishneva; Olga S. Gundobina; Elena A. Dobrynina; Ekaterina Yu. Zaharova; Elena V. Kaytukova; Elena V. Komarova; Sergey I, Kutsev; Alla E. Lavrova; et al. (Педиатрическая фармакология, 2024)
This article presents data on the epidemiology, pathogenesis, modern classification and the main clinical manifestations of Gaucher disease in children. The criteria for differential diagnosis with other diseases are given. It has been shown that the only effective method of treating Gaucher disease is pathogenetic enzyme replacement therapy, which relieves the main clinical manifestations of the disease, improving the quality of life of patients and without having pronounced side effects. The main errors of diagnosis and management of patients, as well as unjustified prescriptions for the treatment of this disease, are indicated.